Herpes Zoster and the Risk of Stroke in Patients With Autoimmune Diseases. Issue 2 (February 2017) - Calabrese, Leonard H.; Xie, Fenglong; Yun, Huifeng; Winthrop, Kevin L.; Baddley, John W.; Calabrese, Cassandra; Curtis, Jeffrey R.
Abstract : Objective: Herpes zoster (HZ) is an opportunistic infection caused by varicella‐zoster virus and observed with increasing frequency in patients receiving immunosuppressive therapies. The literature has suggested that the risk of stroke may increase shortly after HZ, but little is known about this association in patients with autoimmune diseases, who are at increased risk of both zoster and stroke. Methods: Medicare data from January 1, 2006 through December 31, 2013 were used to identify patients with autoimmune diseases. The outcome of interest was hospitalized stroke. The hypothesis tested was that the incidence of stroke immediately following HZ is increased compared to the incidence of stroke at later time points. Secondary analyses included assessment of the impact of antiviral therapy on subsequent stroke, as well as the influence of varicella‐zoster virus–related complications on stroke incidence. Results: The crude incidence of stroke ranged from a high of 2.30 per 100 patient‐years (95% confidence interval [95% CI] 0.96–5.52) within 90 days of HZ in patients who had HZ‐related cranial nerve complications and did not receive treatment to a low of 0.87 per 100 patient‐years (95% CI 0.75–1.02) at 366–730 days in those without complication who received antiviral treatment. After multivariable adjustment for multiple stroke‐related factors, the overall incidence rate ratio (IRR) for stroke in the first 90 days after HZ was 1.36 (95% CI 1.10–1.68) compared to stroke occurring at 366–730 days after HZ. The risk was greater for patients with zoster and cranial nerve complications (IRR 2.08 [95% CI 0.99–4.36]). Prompt antiviral therapy was associated with lower incidence of subsequent stroke (IRR 0.83 [95% CI 0.70–0.98]). Conclusion: In patients with autoimmune diseases, incident HZ was associated with as much as a 2‐fold increased risk of stroke in the subsequent few months. These data underscore the urgency of developing strategies for reducing the risk of varicella‐zoster virus.